A method for preparing highly soluble industrial molybdenum oxide from undried molybdenum concentrate containing copper, rhenium and carbon by wet method
Through wet pressurized oxidation treatment and resource recovery technology of molybdenum concentrate containing copper-rhenium carbon, the problem of low resource utilization efficiency after roasting of molybdenum concentrate is solved, and efficient preparation of high-soluble industrial molybdenum oxide and efficient recovery of metal resources are achieved.
Patent Information
- Application Number
- CN202411246847.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-06
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-09-06
AI Technical Summary
In the preparation of industrial molybdenum oxide from molybdenum concentrate, the problem of low molybdenum recovery rate, difficulty in producing acid in low concentration SO2, and environmental pollution. In particular, low grade molybdenum concentrate cannot be used as industrial molybdenum oxide after roasting, and the resource utilization efficiency is low.
The undried molybdenum concentrate containing copper-rhenium carbon is used for wet pressurized oxidation treatment. Through ball milling and pressurized oxidation processes, the leaching rate of molybdenum is inhibited, the molybdenum content of high-soluble industrial molybdenum oxide is increased, and the copper, rhenium and sulfur resources are recovered through extraction method, acid precipitation method and ion adsorption separation.
It has achieved efficient preparation of low-grade molybdenum concentrate to meet the standards and high-soluble industrial molybdenum oxide, while improving the recovery rate of copper, rhenium and sulfur resources, reducing the carbon content in the product, and its simple process is suitable for large-scale industrial production.
Smart Images

Figure CN119082502B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of hydrometallurgy, and in particular to a method for preparing highly soluble industrial molybdenum oxide by hydroprocessing of undried molybdenum concentrate containing copper, rhenium and carbon. Background Art
[0002] Due to the low grade of molybdenum in natural ores, most molybdenum concentrates contain 45% to 51% Mo; while the Mo content in the grade standard of "Molybdenum Concentrate Quality Standard GB3200-89" is not less than 45%, 47%, 49%, 51% and 53%. The copper content of molybdenum concentrate from single molybdenum ore flotation is 0.28%, 0.25%, 0.22%, 0.2% and 0.15% for different Mo content grades, and the copper content of molybdenum concentrate from comprehensive recovery and flotation of polymetallic ores is 1.2%, 0.8%, 0.6%, 0.4% and 0.2% for different Mo content grades.
[0003] The roasting problem from molybdenum concentrate to industrial molybdenum oxide has always been a bottleneck restricting the production of molybdenum oxide. The main processes currently used are multi-hearth furnace roasting process, rotary kiln roasting process, reverberatory furnace roasting process, etc. Foreign countries mostly use multi-hearth furnace roasting process. Multi-hearth furnaces generally have 8 to 16 layers. The residence time of the charge in the furnace can be adjusted by driving the rake teeth through the rotating shaft. For multi-hearth furnace roasting, molybdenum concentrate is added from the top layer and is oxidized by the oxygen in the rising hot air flow during the continuous flipping and falling process. The air is introduced from the bottom layer or in layers, and the exhaust gas is discharged from the top or in layers. During the roasting process, the charge and the gas are in countercurrent contact and well mixed, the oxidation reaction is fully carried out, the desulfurization effect and product quality are good, and the production capacity is also large. Most domestic companies use the rotary kiln process. During roasting, the material moves from the kiln tail to the kiln head under the rotation and tilting of the kiln body, and the molybdenite begins to undergo oxidation reaction. The material is easy to agglomerate, and the oxidation is incomplete and uneven. The fuel flue gas and the process flue gas are discharged from different flues, and the SO in the exhaust gas 2 The concentration is high, about 0.07% to 0.08%, but it is still not suitable for acid production. Compared with multi-chamber furnaces, rotary kilns have a shorter construction period and a slightly lower cost, but the kiln body is easily burned, resulting in a shorter service life of the rotary kiln (generally 2 to 5 months), incomplete oxidation of molybdenum concentrate, and difficulty in removing sulfur and metal impurities in oxidized molybdenum.
[0004] Roasted molybdenum concentrate is industrial molybdenum oxide. The minimum grade of roasted molybdenum concentrate (high soluble) YMo-53 in "Roasted Molybdenum Concentrate GB / T24482-2009" stipulates that Mo≥53%, Cu≤0.26%, and S≤0.3%. The product particle size of roasted molybdenum concentrate (high soluble) is ≤5mm. When the molybdenum concentrate is roasted, the roasting yield is about 90%, that is, the Mo content increases by about 5%. Therefore, to meet the Mo≥53 requirement of the minimum grade of industrial molybdenum oxide YMo-53, the molybdenum concentrate raw material must meet Mo≥49%, and at the same time meet the Cu≤0.26% of the minimum grade of industrial molybdenum oxide YMo-53, the molybdenum concentrate raw material needs Cu≤0.22%.
[0005] Therefore, only the molybdenum concentrate grade with a standard Mo content of not less than 49%, 51% and 53% from the flotation of a single molybdenum ore, and the molybdenum concentrate grade with a standard Mo content of not less than 53% from the comprehensive recovery and flotation of polymetallic ores can meet the requirements for roasting to prepare industrial molybdenum oxide. However, most low-content molybdenum, especially molybdenum concentrates with Mo<45% and high copper content and associated rhenium, cannot be sold as industrial molybdenum oxide to produce iron-molybdenum alloys or other steel products after roasting. It can only be used to produce molybdenum chemical products such as ammonium molybdate, or to further produce high-purity molybdenum oxide, molybdenum powder and other products. However, the consumption of molybdenum is mainly in the form of industrial molybdenum oxide, and its application areas and distribution ratios are roughly as follows: steel smelting consumption accounts for about 80%, molybdenum chemical products account for about 12%, and metal molybdenum products account for about 8%.
[0006] The preparation of industrial molybdenum oxide from molybdenum concentrate by pyro-roasting has the following problems: low molybdenum recovery rate and low concentration of SO 2 The pressurized wet process has the disadvantages of being difficult to produce acid and causing environmental pollution. The pressurized wet process has attracted wide attention due to its short process, high metal recovery rate, strong raw material adaptability and environmental friendliness.
[0007] The POX (Oxygen Pressure Oxidation) wet process of molybdenum concentrate is an oxidation decomposition reaction of molybdenum concentrate under a certain temperature and oxygen pressure. Almost all the molybdenum sulfides in the concentrate are oxidized, and the sulfur enters the leaching solution in the form of sulfuric acid. About 80% of the molybdenum is in the form of H 2 MoO 4 or MoO 3 The form remains in the solid phase, and the rest is MoO 2 (SO 4 ) or Mo 2 O 5 (SO 4 ) form into the solution.
[0008] For molybdenum ores that are difficult to be selected in the comprehensive recovery of polymetallic ores, a low-grade molybdenum middling ore that is difficult to be recovered by flotation method is often produced during the beneficiation process; some molybdenum concentrates or low-grade molybdenum concentrates cannot be obtained due to too high impurity content. In particular, molybdenum ore contains carbon, and its main component is graphite. Since the floatability of graphite is equivalent to that of molybdenite, it is difficult to separate it from molybdenite during the beneficiation process, and only molybdenum concentrates with high carbon content can be obtained by beneficiation. The carbon content in molybdenum concentrate is also an important indicator. Carbon phase analysis shows that the carbon in molybdenum concentrate is organic carbon (ore dressing agent kerosene, etc.), inorganic carbon (carbonate), graphite carbon, etc., and organic carbon accounts for about 24%.
[0009] At present, after the general molybdenum concentrate is beneficiated, the product needs to be dried, on the one hand to remove free water, on the other hand to remove the oil attached to the molybdenum concentrate (mainly flotation reagents and a small amount of mechanical oil), one of the main components of flotation reagents is kerosene. The temperature must be controlled above 220℃, and the temperature of molybdenum concentrate drying is generally controlled at 230-300℃. YS / T 555.11-2009 has measurement regulations for the oil and moisture content in molybdenum concentrate. When the molybdenum concentrate is roasted by pyrometallurgy, the oil moisture content of the molybdenum concentrate is too high, the fluidity of the molybdenum concentrate is poor, and it is difficult to add materials, making it difficult to achieve uniform and continuous production. The deoiling and dehydration time is prolonged, which reduces the operating efficiency. Therefore, the oil moisture content of the molybdenum concentrate should generally be controlled below 1% to obtain a better roasting effect.
[0010] The molybdenum concentrate obtained by flotation contains copper, copper-rhenium, or high carbon content, low molybdenum content, and is not dried and deoiled (i.e., de-organic carbon), which makes it difficult to process by pyro-roasting. How to adopt a certain method to make the molybdenum basically remain in the leaching residue after oxidation, so as to obtain a highly soluble industrial molybdenum oxide product, and at the same time, the low content of copper, rhenium, and sulfur resources in the molybdenum concentrate can be oxidized to form a certain concentration of dilute sulfuric acid, so as to realize the transformation of waste into treasure and efficient utilization of resources, has become the focus of research. Summary of the invention
[0011] The purpose of the present application is to provide a method for wet preparation of highly soluble industrial molybdenum oxide from undried molybdenum concentrate containing copper, rhenium and carbon, so as to solve the above problems.
[0012] To achieve the above objectives, this application adopts the following technical solutions:
[0013] A method for preparing highly soluble industrial molybdenum oxide by wet process from undried molybdenum concentrate containing copper, rhenium and carbon, comprising:
[0014] The undried molybdenum concentrate containing copper, rhenium and carbon, sodium sulfide and water are mixed and ball-milled, and then a first solid-liquid separation is performed to obtain ball-milled solids and grinding water;
[0015] The ball-milled solids and water are mixed to prepare a slurry to be treated, the slurry to be treated is preheated and then subjected to pressurized oxidation treatment, and a second solid-liquid separation is performed to obtain the highly soluble industrial molybdenum oxide and a leachate;
[0016] The leachate is extracted by an extraction method to obtain a raffinate, and then stripped to obtain a stripping solution. The stripping solution is treated by an acid precipitation method to obtain ammonium molybdate and an acid precipitation solution. The acid precipitation solution is subjected to ion adsorption separation to enrich rhenium, and the desorption solution is crystallized to prepare ammonium rhenate; the raffinate is subjected to copper sulfide precipitation using sodium thiosulfate to obtain copper sulfide slag and a copper precipitation solution, and the copper precipitation solution is dilute sulfuric acid;
[0017] The carbon content of the undried molybdenum concentrate containing copper-rhenium carbon is 1-5wt%.
[0018] Preferably, the method for preparing highly soluble industrial molybdenum oxide by wet process from undried molybdenum concentrate containing copper, rhenium and carbon satisfies one or more of the following conditions:
[0019] (1) The amount of sodium sulfide used is 1-10wt% of the molybdenum concentrate;
[0020] (2) The slurry concentration of the ball mill is 30-60wt%;
[0021] (3) The ball milling time is 20-180 min;
[0022] (4) The end point of the ball milling is that the proportion of materials with a particle size of less than or equal to 200 mesh accounts for no less than 90% of the total materials.
[0023] Preferably, the solid-liquid ratio of the slurry to be treated is 1 g: (7-14) ml.
[0024] Preferably, the pressure oxidation treatment includes preheating, one-stage pressure oxidation leaching and two-stage pressure oxidation leaching.
[0025] Preferably, the temperature of the material after the preheating is 70-90°C;
[0026] The temperature of the first stage pressurized oxidation leaching is 150-170°C, and the oxygen partial pressure is 0.1-0.3MPa;
[0027] The temperature of the second stage pressurized oxidation leaching is 180-220°C, and the oxygen partial pressure is 0.5-0.8MPa;
[0028] The time of the pressurized oxidation treatment is 5-10h;
[0029] The pressurized oxidation treatment is carried out under stirring, and the stirring linear speed is 3-5 m / s.
[0030] Preferably, the amount of sodium thiosulfate used is 5-50 times the mass of copper in the raffinate.
[0031] Preferably, the reaction temperature of the copper sulfide deposition is 20-80° C. and the reaction time is 1-4 hours.
[0032] Preferably, the grinding water is supplemented with sodium sulfide and water and then returned for the ball milling.
[0033] Preferably, the solid obtained by the second solid-liquid separation is washed and dried to obtain the highly soluble industrial molybdenum oxide;
[0034] The washing water obtained from the washing is returned to prepare the ore pulp to be treated.
[0035] Preferably, the extraction agent used in the extraction method includes 15-30% N235, 10-40% octanol, and the balance is kerosene, and the extraction O / A ratio is 1:6-1:3;
[0036] The extraction method adopts 4-8 level countercurrent extraction;
[0037] The stripping agent used in the stripping is 15-25wt% ammonia water, and the stripping O / A ratio is 3:1-8:1;
[0038] The temperature of the acid precipitation method is 40-60°C, and the end point pH is 2.0-3.0;
[0039] The resin used for ion adsorption includes No. 201 strong alkaline anion exchange resin, and the desorbent used is 1-1.5 mol / L ammonium thiocyanate or sodium thiocyanate.
[0040] Preferably, the molybdenum content in the molybdenum concentrate is not less than 38wt%, the copper content is not less than 0.1wt%, and the rhenium content is not less than 0.001wt%.
[0041] Compared with the prior art, the beneficial effects of this application include:
[0042] The present application provides a method for wet-process preparation of highly soluble industrial molybdenum oxide from undried molybdenum concentrate containing copper, rhenium and carbon. The carbon contained in the molybdenum concentrate is utilized to participate in the pressurized oxidation treatment process without drying, thereby inhibiting the leaching of molybdenum into the solution, thereby realizing the preparation of high-soluble industrial molybdenum oxide that meets the standards from low-grade molybdenum concentrate while reducing the carbon content in the product and separating and utilizing copper and rhenium. On the one hand, the method does not require de-drug treatment by drying or adding other agents, and on the other hand, it does not require separate decarbonization treatment. The preparation process is simple, the recovery rate of molybdenum, rhenium and copper metals is high, and the dilute sulfuric acid of a certain concentration formed after the oxidation of sulfur resources can also be efficiently utilized, and the method is suitable for large-scale industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope of the present application.
[0044] Figure 1 This is a scanning electron microscope image of the undried molybdenum concentrate containing copper-rhenium carbon used in Examples 1 to 3;
[0045] Figure 2 The particle size distribution diagram of the undried molybdenum concentrate containing copper-rhenium carbon used in Examples 1 to 3;
[0046] Figure 3 The present invention is a schematic process flow diagram of a method for preparing highly soluble industrial molybdenum oxide by wet process from undried molybdenum concentrate containing copper, rhenium and carbon provided in an embodiment. DETAILED DESCRIPTION
[0047] In order to better explain the technical solution provided by this application, before the embodiments, the technical solution is first described as a whole, as follows:
[0048] A method for preparing highly soluble industrial molybdenum oxide by wet process from undried molybdenum concentrate containing copper, rhenium and carbon, comprising:
[0049] The undried molybdenum concentrate containing copper, rhenium and carbon, sodium sulfide and water are mixed and ball-milled, and then a first solid-liquid separation is performed to obtain ball-milled solids and grinding water;
[0050] The ball-milled solids and water are mixed to prepare a slurry to be treated, the slurry to be treated is preheated and then subjected to pressurized oxidation treatment, and a second solid-liquid separation is performed to obtain the highly soluble industrial molybdenum oxide and a leachate;
[0051] The leachate is extracted by an extraction method to obtain a raffinate, and then stripped to obtain a stripping solution. The stripping solution is treated by an acid precipitation method to obtain ammonium molybdate and an acid precipitation solution. The acid precipitation solution is subjected to ion adsorption separation to enrich rhenium, and the desorption solution is crystallized to prepare ammonium rhenate; the raffinate is subjected to copper sulfide precipitation using sodium thiosulfate to obtain copper sulfide slag and a copper precipitation solution, and the copper precipitation solution is dilute sulfuric acid;
[0052] The carbon content of the undried molybdenum concentrate containing copper-rhenium carbon is 1-5wt%.
[0053] The present application aims at comprehensively recovering undried molybdenum concentrate containing copper, rhenium and carbon from polymetallic ores through flotation, and at the difficulties and shortcomings of existing pyrometallurgical technologies. The pressurized oxidation process of molybdenum concentrate is improved, and a process flow for preparing highly soluble industrial molybdenum oxide by a wet method is provided. At the same time, a method for realizing efficient recovery of copper, rhenium and sulfur resources is provided. In this process, organic carbon is volatilized and removed, and inorganic carbon and graphite carbon are reacted and removed, and the leaching rate of molybdenum is also suppressed.
[0054] The test found that the graphite carbon in the molybdenum concentrate was fully dissociated during ball milling and mechanically activated to a certain extent during ball milling. During pressurized oxidation, the carbon may react with the acid and molybdenum ions in the solution, which can inhibit the entry of molybdenum into the solution, reduce the leaching rate of molybdenum, enrich molybdenum in the leaching residue, and increase the molybdenum content of high-soluble industrial molybdenum oxide.
[0055] When extracting molybdenum and rhenium, copper is not extracted. The copper content in the raffinate is the same as that in the leaching solution. Sodium thiosulfate (Na 2 S 2 O 3 ) to sulfide copper precipitation, obtain copper sulfide slag, sell it to copper smelters, and realize copper recovery. The liquid after copper precipitation is a certain concentration of dilute sulfuric acid, which can be used as an acidic leaching agent to achieve efficient utilization of sulfur resources.
[0056] Optionally, the carbon content of the undried molybdenum concentrate containing copper-rhenium-carbon may be 1wt%, 2wt%, 3wt%, 4wt%, 5wt% or any value between 1-5wt%.
[0057] In an optional embodiment, the method for preparing highly soluble industrial molybdenum oxide by wet process from undried molybdenum concentrate containing copper, rhenium and carbon satisfies one or more of the following conditions:
[0058] (1) The amount of sodium sulfide used is 1-10wt% of the molybdenum concentrate;
[0059] (2) The slurry concentration of the ball mill is 30-60wt%;
[0060] (3) The ball milling time is 20-180 min;
[0061] (4) The end point of the ball milling is that the proportion of materials with a particle size of less than or equal to 200 mesh accounts for no less than 90% of the total materials.
[0062] Optionally, the amount of the sodium sulfide can be 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt% or any value between 1-10wt% of the molybdenum concentrate; the slurry concentration of the ball milling can be 30wt%, 40wt%, 50wt%, 60wt% or any value between 30-60wt%; the ball milling time can be 20min, 40min, 60min, 80min, 100min, 120min, 140min, 160min, 180min or any value between 20-180min; the endpoint of the ball milling can be any value of 90%, 91%, 92%, 93%, 94%, 95%, 96%, 97%, 98%, 99%, 100% or not less than 90% of the proportion of materials with a particle size less than or equal to 200 mesh in the total material.
[0063] In an optional embodiment, the solid-liquid ratio of the slurry to be treated is 1g: (7-14)ml.
[0064] Selecting a large liquid-to-solid ratio, on the one hand, is to have a low slurry concentration, which is conducive to the dispersion of oxygen and the contact reaction of minerals. On the other hand, a large liquid-to-solid ratio and a low sulfuric acid concentration in the leaching solution can reduce the leaching rate of molybdenum, enrich molybdenum in the leaching residue, and increase the molybdenum content of highly soluble industrial molybdenum oxide.
[0065] Optionally, the solid-to-liquid ratio of the slurry to be treated may be 1g:7ml, 1g:8ml, 1g:9ml, 1g:10ml, 1g:11ml, 1g:12ml, 1g:13ml, 1g:14ml or any value between 1g:(7-14)ml.
[0066] In an optional embodiment, the pressure oxidation treatment includes preheating, one-stage pressure oxidation leaching and two-stage pressure oxidation leaching.
[0067] The preheating of the slurry to be treated is to use the heat of the slurry after the pressurized oxidation treatment. Specifically: after the pressurized oxidation treatment, the slurry enters the flash tank through self-pressure to cool down. The working temperature is 120-150℃, and flash steam is generated at the same time to preheat the slurry to be treated.
[0068] Intermittent small-scale tests show that the initial oxidation temperature of copper-rhenium is about 150°C, that is, at this temperature, copper-rhenium sulfide reacts with the oxygen introduced to generate copper sulfate and perrhenic acid into the solution. The initial oxidation temperature of molybdenum is about 170°C, that is, at this temperature, the main phase of molybdenum sulfide in the molybdenum concentrate begins to react with the oxygen introduced, and most of it is oxidized to MoO 3 Enter into the slag, and at the same time a small amount of MoO 2 (SO 4 ) 2 2- The anion form enters the solution. After oxygen is introduced at 150°C, a chemical reaction occurs. The heat of the chemical reaction causes the temperature to rise rapidly to about 170°C, causing the oxidation reaction of molybdenum to occur, while continuing to self-heat and raise the temperature. In an industrial continuous pressurized reactor, it can be roughly divided into two stages. The precise control of the self-heating energy of the oxidation process of molybdenum concentrate is achieved through the differences in slurry feed rate (calculated and determined according to the processing capacity of the autoclave and the reaction time), oxygen introduction rate and addition amount (oxygen partial pressure and time), stirring line speed, etc. Taking the five reaction chambers of the autoclave as an example, the first reaction chamber is a one-stage leaching, which is mainly the oxidation leaching of sulfides such as copper and rhenium; the second to fifth reaction chambers are two-stage leaching, which is mainly the oxidation leaching of molybdenum sulfides.
[0069] In an optional embodiment, the temperature of the material after the preheating is 70-90°C;
[0070] The temperature of the first stage pressurized oxidation leaching is 150-170°C, and the oxygen partial pressure is 0.1-0.3MPa;
[0071] The temperature of the second stage pressurized oxidation leaching is 180-220°C, and the oxygen partial pressure is 0.5-0.8MPa;
[0072] The pressure oxidation treatment time is 5-10h;
[0073] The pressurized oxidation treatment is carried out under stirring, and the stirring linear speed is 3-5 m / s.
[0074] In order to ensure the safe operation of the autoclave and the oxidation effect of the molybdenum concentrate, the pressurized oxidation leaching time is controlled to 5-10h. The test found that if the oxygen partial pressure is too high, the reaction time can be appropriately shortened, but the reaction occurs too quickly, the heat is released too quickly, the local temperature of the autoclave is too high, the pressure increases, and the safety and operation difficulty of the autoclave are increased. If the autoclave can self-heat to the required temperature, the oxidation effect of the molybdenum concentrate can be achieved by extending the time, so the leaching time is selected to be more than 5h.
[0075] Optionally, the temperature of the first stage pressurized oxidation leaching can be 150°C, 160°C, 170°C or any value between 150-170°C, and the oxygen partial pressure can be 0.1MPa, 0.2MPa, 0.3MPa or any value between 0.1-0.3MPa; the temperature of the second stage pressurized oxidation leaching can be 180°C, 190°C, 200°C, 210°C, 220°C or any value between 180-220°C, and the oxygen partial pressure can be 0.5MPa, 0.6MPa, 0.7MPa, 0.8MPa or any value between 0.5-0.8MPa; the time of the pressurized oxidation treatment can be 5h, 6h, 7h, 8h, 9h, 10h or any value between 5-10h; the pressurized oxidation treatment is carried out under stirring, and the stirring linear speed can be 3m / s, 4m / s, 5m / s or any value between 3-5m / s.
[0076] In an optional embodiment, the amount of sodium thiosulfate used is 5-50 times the mass of copper in the raffinate.
[0077] Optionally, the amount of the sodium thiosulfate used can be 5 times, 10 times, 20 times, 30 times, 40 times, 50 times or any value between 5 and 50 times the mass of the copper in the raffinate.
[0078] In an optional embodiment, the reaction temperature of the copper sulfide deposition is 20-80° C. and the time is 1-4 hours.
[0079] Optionally, the reaction temperature of the copper sulfide deposition can be 20°C, 30°C, 40°C, 50°C, 60°C, 70°C, 80°C or any value between 20-80°C, and the reaction time can be 1h, 2h, 3h, 4h or any value between 1-4h.
[0080] In an optional embodiment, the grinding water is supplemented with sodium sulfide and water and then returned for the ball milling.
[0081] Generally, after the solid-liquid separation of the ball mill slurry, ball mill filter cake and grinding water are obtained. The filter cake contains about 20% water, and the grinding water can be recycled after adding sodium sulfide and water.
[0082] In an optional embodiment, the solid obtained by the second solid-liquid separation is washed and dried to obtain the highly soluble industrial molybdenum oxide;
[0083] The washing water obtained from the washing is returned to prepare the ore pulp to be treated.
[0084] In an optional embodiment, the extractant used in the extraction method is calculated by volume percentage, including 15-30% N235, 10-40% octanol, and the balance is kerosene; the extraction O / A ratio is 1:6-1:3;
[0085] The extraction method adopts 4-8 level countercurrent extraction;
[0086] The stripping agent used in the stripping is 15-25wt% ammonia water, and the stripping O / A ratio is 3:1-8:1;
[0087] The temperature of the acid precipitation method is 40-60°C, and the end point pH is 2.0-3.0;
[0088] The resin used for ion adsorption includes No. 201 strong alkaline anion exchange resin, and the desorbent used is 1-1.5 mol / L ammonium thiocyanate or sodium thiocyanate.
[0089] Optionally, in the extractant, the volume of N235 can be 15 vol%, 20 vol%, 25 vol%, 30 vol% or any value between 15-30 vol%, the volume of 2-octanol can be 10 vol%, 15 vol%, 20 vol%, 25 vol%, 30 vol%, 35 vol%, 40 vol% or any value between 15-40 vol%, and the balance is kerosene; the extraction O / A ratio can be 1:3, 1:4, 1:5, 1:6 or 1:6- 1:3; the number of countercurrent extraction stages used in the extraction method can be 4, 5, 6, 7 or 8; the stripping agent used in the stripping is ammonia water, the ammonia water concentration can be 15wt%, 20wt%, 25wt% or any value between 15-25wt%, the stripping O / A ratio can be 3:1, 4:1, 5:1, 6:1, 7:1, 8:1 or any value between 3:1-8:1; the temperature of the acid precipitation method can be 40°C, 45°C, 50°C, 55°C, 60°C or any value between 40-60°C, and the endpoint pH can be 2.0, 2.5, 3.0 or any value between 2.0-3.0; the concentration of the desorbent can be 1mol / L, 1.1mol / L, 1.2mol / L, 1.3mol / L, 1.4mol / L, 1.5mol / L or any value between 1-1.5mol / L.
[0090] In an optional embodiment, the molybdenum content in the molybdenum concentrate is not less than 38wt%, the copper content is not less than 0.1wt%, and the rhenium content is not less than 0.001wt%.
[0091] The embodiments of the present application will be described in detail below in conjunction with specific examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. If specific conditions are not specified in the examples, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0092] First, the composition of the undried molybdenum concentrate containing copper-rhenium carbon used in the embodiment is described, as shown in Table 1 below:
[0093] Table 1 Chemical composition of undried molybdenum concentrate containing copper, rhenium and carbon
[0094]
[0095] Scanning electron microscope image of undried molybdenum concentrate containing copper, rhenium and carbon is shown in Figure 1 As shown, the carbon in molybdenum concentrate mainly exists in the form of graphite with low degree of crystallization or amorphous carbon, and is mostly produced in the form of fine-grained monomers. The particle size of carbonaceous embedding is mostly less than 0.038mm (i.e. 400 mesh), and some are coarser.
[0096] The particle size distribution of undried molybdenum concentrate containing copper, rhenium and carbon is shown in Figure 2 shown.
[0097] In order to illustrate the effect of ball milling time on particle size, the following test was conducted:
[0098] The undried molybdenum concentrate containing copper, rhenium and carbon was prepared into 40% slurry, and 2% sodium sulfide was added for ball milling for 30min, 60min, 90min and 120min. The particle size distribution at this time is shown in Table 2. As the grinding time increases, the particle size does not increase significantly.
[0099] Table 2 Grinding time and particle size distribution data
[0100]
[0101] 100g of ground sample was prepared into a slurry with a liquid-solid ratio of 8:1, and pressurized oxidation leaching was carried out in a small pressure autoclave. The first stage of pressurized oxidation temperature was controlled to be 150℃, the oxygen partial pressure was 0.1MPa, the heating time was about 50min, and the insulation reaction time was 0.5h. The temperature was continued to rise for about 30min, and the second stage of pressurized oxidation temperature was controlled to be 210℃, the oxygen partial pressure was 0.6MPa, and the reaction time was 5h. The slag rate and the content of molybdenum, rhenium, copper and sulfur in the pressurized leaching slag were analyzed. The leaching rate of rhenium, the leaching rate of copper, the conversion rate of molybdenum, the leaching rate of molybdenum, the leaching rate of molybdenum, the molybdenum content in the leaching slag, the alkali solubility of molybdenum, and the S content in the leaching slag are shown in Table 3, which meets the standard requirement of S content ≤0.3% for high-soluble industrial molybdenum oxide. As the grinding time increases, the carbon content in the slag decreases, the leaching rate of molybdenum decreases, and the molybdenum content in the slag increases.
[0102] Table 3 Test results of pressure oxidation of molybdenum concentrate at different ball milling times
[0103]
[0104] In order to illustrate the effect of solid-liquid ratio on leaching, the following test was conducted:
[0105] The undried copper-rhenium-molybdenum concentrate was prepared into a 50% slurry, and 2% sodium sulfide was added and ball milled for 60 minutes.
[0106] 100g of ground sample was prepared into slurry with solid-liquid ratio of 1:6, 1:7, 1:8, 1:10, 1:12, and pressure oxidation leaching was carried out in a small pressure autoclave. The temperature of the first pressure oxidation was controlled to be 160℃, the oxygen partial pressure was 0.2MPa, and the heat preservation reaction time was 1h. The temperature was continued to rise, and the temperature of the second pressure oxidation was controlled to be 210℃, the oxygen partial pressure was 0.6MPa, and the reaction time was 5h. The slag rate and the content of molybdenum, rhenium, copper and sulfur in the pressure leaching slag were analyzed. The leaching rate of rhenium, the leaching rate of copper, the conversion rate of molybdenum, the leaching rate of molybdenum, the leaching rate of molybdenum, the molybdenum content in the leaching slag, the alkali solubility of molybdenum, and the S content in the leaching slag are shown in Table 4. When the solid-liquid ratio is 1:6, due to incomplete oxidation, the sulfur content in the slag is high and the conversion rate of molybdenum is also low. When the solid-liquid ratio is above 1:7, it meets the standard requirement of S content ≤ 0.3% for high-soluble industrial molybdenum oxide, and as the liquid-solid ratio increases, the carbon content in the slag decreases, the molybdenum leaching rate decreases, and the molybdenum content in the slag increases. Therefore, the test needs to select a solid-liquid ratio of 1:7 or above.
[0107] Table 4 Test results of pressure oxidation of molybdenum concentrate with different liquid-solid ratios
[0108]
[0109] Example 1
[0110] like Figure 3 As shown, this embodiment provides a method for preparing highly soluble industrial molybdenum oxide by wet method from undried molybdenum concentrate containing copper, rhenium and carbon, comprising the following steps:
[0111] (1) Prepare 40% slurry of undried molybdenum concentrate containing copper, rhenium and carbon, add 2% sodium sulfide and grind in a ball mill for 30 minutes, and the particle size of the slurry is less than 200 mesh (74μm) accounting for more than 90%;
[0112] (2) The filter cake after solid-liquid separation of the ball-milled molybdenum concentrate and the washing water of the leached residue are slurried and mixed evenly at a solid-liquid ratio of 1g:8ml;
[0113] (3) Under the condition of oxygen flow in the autoclave, pressurized oxidation leaching was carried out, the temperature of the first stage was controlled at 150°C, the oxygen partial pressure was controlled at 0.1MPa, and the reaction time was 0.5h; the temperature of the second stage was 210°C, the oxygen partial pressure was controlled at 0.6MPa, and the reaction time was 5h, to obtain a leaching solution containing molybdenum-rhenium copper and a leaching residue with high solubility in industrial molybdenum oxide, analyze the content of each element in the leaching residue, and calculate the leaching rate;
[0114] (4) The sulfuric acid content in the pressurized leaching solution is 125g / L. The pressurized leaching solution uses 20v% N235+10v% octanol+70v% kerosene, extracts O / A 1:4, and extracts molybdenum and rhenium in 4-stage countercurrent. Then, 20wt% ammonia water is used, and the O / A ratio is 6:1. After the molybdenum and rhenium are stripped, sulfuric acid is used to acid-precipitate molybdenum at a temperature of 40°C and an end point pH of 2.5 to prepare ammonium molybdate. The acid precipitation solution uses 701201 strong alkaline anion exchange resin for ion adsorption, and the desorbent is 1mol / L ammonium thiocyanate. The desorbed solution is used to prepare ammonium rhenate through secondary crystallization.
[0115] (5) The raffinate is treated with sodium thiosulfate (Na 2 S 2 O 3 )Copper sulfide, Na 2 S 2 O 3 The amount added was 10 times the amount of copper in the raffinate (mass ratio), the reaction temperature was 60°C, the time was 3h, and the copper precipitation rate was 98.2%.
[0116] Example 2
[0117] The difference from Example 1 is:
[0118] The sulfuric acid content in the pressurized leaching solution after ball milling for 120 minutes is 137g / L. The pressurized leaching solution uses 18v%N235+10v%octanol+72v%kerosene, extracts O / A 1:3, and extracts molybdenum and rhenium in 5-stage countercurrent. After the molybdenum and rhenium are stripped with 22wt% ammonia water and the O / A ratio is 7:1, the molybdenum is acid-precipitated with sulfuric acid at a temperature of 50°C and an end point pH of 2.7 to prepare ammonium molybdate. The acid precipitation solution uses No. 201 strong alkaline anion exchange resin for ion adsorption, and the desorbent is 1.3mol / L ammonium thiocyanate. The desorbed solution is used to prepare ammonium rhenate by secondary crystallization.
[0119] The raffinate was treated with sodium thiosulfate (Na 2 S 2 O 3 )Copper sulfide, Na 2 S 2 O 3 The added amount was 20 times (mass ratio) of the copper amount in the raffinate, the reaction temperature was 80°C, the time was 2h, and the copper precipitation rate was 99.1%.
[0120] Example 3
[0121] According to the results in Table 4, the sulfuric acid content in the pressurized leaching solution with a solid-liquid ratio of 1:10 is 100.34 g / L. The pressurized leaching solution uses 25 v% N235 + 15 v% octanol + 60 v% kerosene, extracts O / A 1:5, and extracts molybdenum and rhenium in 7-stage countercurrent. After the molybdenum and rhenium are stripped with 18 wt% ammonia water and the O / A ratio is 5:1, the molybdenum is acid-precipitated with sulfuric acid at a temperature of 50 ° C and an end point pH of 2.8 to prepare ammonium molybdate. The acid precipitation liquid uses No. 201 strong alkaline anion exchange resin for ion adsorption, and the desorbent is 1.2 mol / L sodium thiocyanate. The desorbent is prepared by secondary crystallization to prepare ammonium rhenate.
[0122] The raffinate was treated with sodium thiosulfate (Na 2 S 2 O 3 ) Sulfide copper, Na 2 S 2 O 3 The amount added was 15 times the amount of copper in the raffinate (mass ratio), the reaction temperature was 40°C, the time was 1h, and the copper precipitation rate was 99.2%.
[0123] Comparative Example 1
[0124] The undried molybdenum concentrate containing copper, rhenium and carbon was prepared into a 50% slurry and ball-milled for 60 minutes without adding sodium sulfide.
[0125] 100g of ground sample was prepared into slurry with liquid-solid ratio of 8:1 and 10:1, and pressurized oxidation leaching was carried out in a small pressure autoclave. The temperature of the first stage of pressure oxidation was controlled to be 160℃, the oxygen partial pressure was 0.2MPa, and the heat preservation reaction time was 1h. The temperature was continued to rise, and the temperature of the second stage of pressure oxidation was controlled to be 210℃, the oxygen partial pressure was 0.6MPa, and the reaction time was 5h. The slag rate of the pressure leaching slag and the content of each element of molybdenum, rhenium, copper and sulfur were analyzed. The leaching rate of rhenium, the leaching rate of copper, the conversion rate of molybdenum, the leaching rate of molybdenum, the leaching rate of molybdenum, the molybdenum content in the leaching slag, the alkali solubility of molybdenum, and the S content in the leaching slag are shown in Table 5. It can be seen from the experiment that the pressure oxidation effect of the molybdenum concentrate ground sample without the addition of sodium sulfide is relatively poor under the same conditions. Especially when the liquid-solid ratio is 8, the sulfur content in the slag is 0.11%, and the oxidation is not complete. Therefore, adding sodium sulfide can break the influence of organic carbon, facilitate gas-solid contact during the reaction, and make the reaction proceed thoroughly.
[0126] Table 5 Test results of pressure oxidation of molybdenum concentrate with different liquid-solid ratios
[0127]
[0128] Comparative Example 2
[0129] The undried molybdenum concentrate containing copper, rhenium and carbon was prepared into a 50% slurry, and 2% sodium sulfide was added and ball milled for 60 minutes.
[0130] 100g of ground sample was prepared into a slurry with a liquid-solid ratio of 8:1, and pressurized oxidation leaching was carried out in a small pressure autoclave. The first stage of pressure oxidation temperature was controlled to be 160℃, the oxygen partial pressure was 0.2MPa, and the heat preservation reaction time was 1h. The temperature was continued to rise, and the second stage of pressure oxidation temperature was controlled to be 210℃, the oxygen partial pressure was 0.6MPa, and the reaction time was 3h. The slag rate of the pressure leaching slag and the content of each element of molybdenum, rhenium, copper and sulfur were analyzed. The leaching rate of rhenium, the leaching rate of copper, the conversion rate of molybdenum, the leaching rate of molybdenum, the molybdenum content in the leaching slag, the alkali solubility of molybdenum, and the S content in the leaching slag are shown in Table 6. When the temperature was kept for 3h, the sulfur content in the slag was 2.44%. Due to incomplete oxidation, the conversion rate of molybdenum was also low, which was 96.92%. Therefore, the reaction time is more than 5h to make the oxidation reaction of molybdenum concentrate complete.
[0131] Table 6 Test results of pressure oxidation of molybdenum concentrate with a holding time of 3h
[0132]
[0133] Comparative Example 3
[0134] The test selected molybdenum concentrate No. 2 sample with high molybdenum content (composition see Table 7), with carbon content less than 0.5%, and the particle size below 200 mesh accounted for 93.6%, and below 400 mesh accounted for 70.6%.
[0135] Table 7 Composition of molybdenum concentrate sample No. 2
[0136]
[0137] At a reaction temperature of 200°C, a liquid-to-solid ratio of 7, a reaction time of 5 hours, and an oxygen partial pressure of 0.6 MPa, the test results are shown in Table 8 below. The molybdenum leaching rate is 19.62%, and the molybdenum content in the leached residue increases by about 8%, which cannot meet the national standard requirement of a molybdenum content greater than 53%.
[0138] Table 8 Test results
[0139]
[0140] Example 4
[0141] In the test, sample No. 3 of copper-rhenium-carbon-molybdenum concentrate was taken and mixed with the test sample used in the above embodiment at a ratio of 1:1. The specific chemical analysis results are shown in Table 9.
[0142] Table 9 Chemical composition of copper-rhenium-carbon-molybdenum concentrate No. 3 and mixed samples
[0143]
[0144] The two undried copper-rhenium-molybdenum concentrates were mixed into a 40% slurry, and 3% sodium sulfide was added and ball milled for 30 minutes.
[0145] 100g of ground sample was prepared into a slurry with a liquid-solid ratio of 9:1, and pressure oxidation leaching was carried out in a small pressure autoclave. The temperature of the first pressure oxidation was controlled to be 180℃, the oxygen partial pressure was 0.2MPa, and the heat preservation reaction time was 1h. The temperature was continued to rise, and the second pressure oxidation temperature was controlled to be 220℃, the oxygen partial pressure was 0.5MPa, and the reaction time was 6h. The slag rate of the pressure leaching slag and the content of each element of molybdenum, rhenium, copper and sulfur were analyzed. The leaching rate of rhenium, the leaching rate of copper, the conversion rate of molybdenum, the leaching rate of molybdenum, the molybdenum content in the leaching slag, the alkali solubility of molybdenum, and the S content in the leaching slag are shown in Table 10.
[0146] Table 10 Molybdenum concentrate batching test results
[0147]
[0148] The sulfuric acid content in the pressurized leaching solution with a liquid-solid ratio of 9:1 is 111.63g / L. The pressurized leaching solution uses 22v%N235+25v%octanol+53v%kerosene, extracts O / A 1:5, and extracts molybdenum and rhenium in 8-stage countercurrent. After the molybdenum and rhenium are stripped with 25wt% ammonia water and the O / A ratio is 8:1, the molybdenum is acid-precipitated with sulfuric acid at a temperature of 60°C and an end point pH of 2.8 to prepare ammonium molybdate. The acid precipitation liquid uses No. 201 strong alkaline anion exchange resin for ion adsorption, and the desorbent is 1.5mol / L sodium thiocyanate. The desorbed liquid is used to prepare ammonium rhenate through secondary crystallization.
[0149] The raffinate was treated with sodium thiosulfate (Na 2 S 2 O 3 ) High acid copper precipitation, the amount added is 8 times the amount of copper in the raffinate (mass ratio), the reaction temperature is 30℃, the time is 2h, and the copper precipitation rate is 97.8%.
[0150] The method provided in this application has the following characteristics: 1. It has strong adaptability to raw materials. Molybdenum concentrate can be recycled without special restrictions on copper content (roasting molybdenum concentrate requires Cu to be less than 0.2%), and rhenium content can reach industrial grade 0.001-0.002% or more. In order to ensure that the molybdenum content of the pressure leaching slag (high-soluble industrial molybdenum oxide) is ≥53%, the molybdenum content in the slag of this application can be increased by 10-15%, so the molybdenum content of the molybdenum concentrate raw material can be ≥38% (compared with the prior art, this application can use raw materials with lower molybdenum content to prepare products that meet the requirements of high-soluble industrial molybdenum oxide, expanding the optional sources of raw materials), and molybdenum concentrates with different molybdenum contents can be used for batching, and only the molybdenum content needs to be examined, without considering the copper-rhenium content. 2. Ball milling with sodium sulfide can make the particle size of molybdenum concentrate finer, further dissociate and mechanically activate the graphite carbon in the molybdenum concentrate, which is beneficial to the mineral oxidation reaction, and the copper-rhenium leaching rate is more than 99%. At the same time, the membrane separation of kerosene and other mineral processing agents in the molybdenum concentrate is achieved, which is beneficial to the contact between oxygen and minerals in the pressure kettle. 3. In the pressurized oxidation process, the technical indicators of molybdenum-rhenium-copper recovery are good, the copper and rhenium leaching rates are more than 99%, the molybdenum conversion rate is more than 99%, the molybdenum leaching rate is ≤12%, the molybdenum content in the high-soluble industrial oxidation molybdenum product is ≥53%, the alkaline solubility of molybdenum is >98%, and the sulfur content in the slag is ≤0.1%. 4. In the pressurized oxidation process, the organic carbon in the molybdenum concentrate will be volatilized and removed, and the inorganic carbon and graphite carbon can be reacted and removed. At the same time, it is found that the reaction of carbon can inhibit the leaching rate of molybdenum and increase the molybdenum content in the leached slag. To ensure that the carbon content can be reduced to the national standard carbon content of ≤0.1%, the carbon content in the raw material can be between 1-5%, and molybdenum concentrates with different carbon contents can be used for batching. 5. The leaching solution extracts molybdenum and rhenium, and the raffinate is sulfided with sodium thiosulfate to precipitate copper, so that the copper can be recovered in the form of copper sulfide, which is convenient for sale. At the same time, a certain concentration of dilute sulfuric acid solution can be used as an acidic leaching agent to make efficient use of sulfur resources in the molybdenum concentrate.
[0151] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.
Claims
1. A method for preparing highly soluble industrial molybdenum oxide from undried molybdenum concentrate containing copper-rhenium carbon by wet method, characterized in that: include: The undried molybdenum concentrate containing copper, rhenium and carbon, sodium sulfide and water are mixed and ball-milled, and then a first solid-liquid separation is performed to obtain ball-milled solids and grinding water; The ball-milled solids and water are mixed to prepare a slurry to be treated, the slurry to be treated is preheated and then subjected to pressurized oxidation treatment, and a second solid-liquid separation is performed to obtain the highly soluble industrial molybdenum oxide and a leachate; The leachate is extracted by an extraction method to obtain a raffinate, and then stripped to obtain a stripping solution. The stripping solution is treated by an acid precipitation method to obtain ammonium molybdate and an acid precipitation solution. The acid precipitation solution is subjected to ion adsorption separation to enrich rhenium, and the desorption solution is crystallized to prepare ammonium rhenate; the raffinate is subjected to copper sulfide precipitation using sodium thiosulfate to obtain copper sulfide slag and a copper precipitation solution, and the copper precipitation solution is dilute sulfuric acid; The carbon content of the undried molybdenum concentrate containing copper, rhenium and carbon is 1-5wt%; the molybdenum content in the molybdenum concentrate is not less than 38wt%, the copper content is not less than 0.1wt%, and the rhenium content is not less than 0.001wt%; The amount of sodium sulfide is 1-10wt% of the molybdenum concentrate; The slurry concentration of the ball mill is 30-60wt%; The ball milling time is 20-180min; The end point of the ball milling is that the proportion of materials with a particle size of less than or equal to 200 mesh accounts for no less than 90% of the total materials; The solid-liquid ratio of the slurry to be treated is 1g: (7-14)ml; The pressure oxidation treatment includes preheating, one-stage pressure oxidation leaching and two-stage pressure oxidation leaching; The temperature of the material after the preheating is 70-90°C; The temperature of the first stage pressurized oxidation leaching is 150-170°C, and the oxygen partial pressure is 0.1-0.3MPa; The temperature of the second stage pressurized oxidation leaching is 180-220°C, and the oxygen partial pressure is 0.5-0.8MPa; The time of the pressurized oxidation treatment is 5-10h; The pressurized oxidation treatment is carried out under stirring, and the stirring linear speed is 3-5 m / s.
2. The method for preparing highly soluble industrial molybdenum oxide from molybdenum concentrate containing copper-rhenium carbon without drying according to claim 1, characterized in that: The amount of the sodium thiosulfate used is 5-50 times the mass of the copper in the raffinate.
3. The method for preparing highly soluble industrial molybdenum oxide from molybdenum concentrate containing copper-rhenium carbon without drying according to claim 1, characterized in that: The reaction temperature of the copper sulfide deposition is 20-80° C. and the reaction time is 1-4 hours.
4. The method for preparing highly soluble industrial molybdenum oxide from molybdenum concentrate containing copper-rhenium carbon without drying according to claim 1, characterized in that: The grinding water is supplemented with sodium sulfide and water and then returned to be used for the ball milling; The solid obtained by the second solid-liquid separation is washed and dried to obtain the highly soluble industrial molybdenum oxide; The washing water obtained from the washing is returned to prepare the ore pulp to be treated.
5. The method for preparing highly soluble industrial molybdenum oxide from molybdenum concentrate containing copper-rhenium carbon without drying according to claim 1, characterized in that: The extraction agent used in the extraction method includes 15-30% N235, 10-40% octanol, and the balance is kerosene, calculated by volume percentage; the extraction O / A ratio is 1:6-1:3; The extraction method adopts 4-8 level countercurrent extraction; The stripping agent used in the stripping is 15-25wt% ammonia water, and the stripping O / A ratio is 3:1-8:1; The temperature of the acid precipitation method is 40-60°C, and the end point pH is 2.0-3.0; The resin used for the ion adsorption includes No. 201 strong alkaline anion exchange resin, and the desorbent used is 1-1.5 mol / L ammonium thiocyanate or sodium thiocyanate.
Citation Information
Patent Citations
Method of recycling molybdenum and rhenium from molybdenum concentrate by hydrometallurgy
CN103866142A
Method for comprehensively recycling copper and rhenium from rhenium-rich residues
CN105671323A
Method for extracting molybdenum and rhenium from rhenium and molybdenum containing concentrate
CN108588446A